CHARACTERISTIC OF HIGHER ORDER THINKING SKILLS ASSESSMENT TO THE ENVIRONMENT LESSON - Kusuma Wardany (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2017)
This research is aimed to know the characteristic of Higher Order Thinking Skills assessment. The instrument was arranged based on Development Borg & Gall step. The arrangement of examination draft validated by qualified validator and teacher. Then, examination draft tested to few students in small trial. The trial result analysed as quantitatively used Quest program that used to determine reliability, difficulty level, differ effort, and distractor effectivity. There are some revisions after small trial, and then field trial did. Based on field trial, it is known that assessment instrument of Higher Order Thinking Skills to senior high school students in Surakarta for environment topic, has high validity and reliability with high and enough interpretation score. Inside of environment topic, there are questions with difficulty level of 0,68% difficult 0,68%, 9,65% medium, and 9,6% are easy (multiple choice) 60% difficult, 40% easy (essay), there are some of them that has differ effort with proportion score 6,89% less, 6,20% enough and 6,89% (multiple choice), 40% enough, 51,11% good and 8,88% very good (essay). Result show that instrument of Higher Order Thinking Skillsassessment about environment topic be able to measure higher thinking skill level ofstudents.